Analisis Kebijakan Penanganan Pemilih Terdampak Relokasi di Pulau Rempang Kota Batam pada Pemilu Tahun 2024 - Aldino, Azjandri; Iskandar Zulkarnain; Fauzan, Indra (PERSPEKTIF, 2024)
This research aims to find out how the policy and what are the obstacles faced by the Batam City KPU in handling voters affected by relocation on Rempang Island, Batam City in the 2024 General Election. Policy analysis in this study uses David Easton's theory. Meanwhile, the analysis of the policy's obstacles is generally described based on the data and research results. This research uses descriptive qualitative research methods. The data collection techniques in this research are observation, interviews, and documentation. Data analysis techniques in this study use data condensation, data presentation, and conclusion drawing. And data validity techniques using source triangulation techniques. The results of research and discussion can be seen as input in the form of demands not to shift TPS from the initial plan that received support from various parties at the sub-district level. Then converted in the internal KPU, resulting in the output of not shifting TPS by input from the community. After that, it gets feedback on the high participation of the community in exercising their voting rights. The policy of handling voters affected by relocation in Rempang Island, Batam City in the 2024 General Election is a policy that is more responsive and adaptive to the needs of the community. The resulting policy is not only effective but can also be adjusted based on feedback and changes in the external environment. The constraints faced, namely regulatory constraints, security constraints and administrative constraints.